Effect of Interaction BetwÂ·een Phosphorus and Zink in Some Morphological Features of Two Varieties of Wheat Grown in Gypsum Soil - -Mahmod, A. A.; Al-Saidi, A. J. H .; Saltern, K. A. (Ibn AL-Haitham Journal For Pure and Applied Sciences, 2017)
A biological experirne.rit was CQhducted Â·ll1 the (Ibn- AlÂ Haitham). University of Baghdad for growing seasens on of 2004/2005 (by using gypsum soil taken from Al- Doar area I Salah AlÂ Dean provinc) to stuclÂ·- the effect three levels of phosphorus (0, 400, SOO)rng ! pot and four levels of zinc (0, 10,.. J 5, 2.0) tngf I pot on some features of two varieties -Qf wheat, (triticum aestivurn var. rateh)and (Triticum aestiv1lm Var. Ipa 99).. R’t:sul.ts o:f experiment showed comparative wheat verities in those features studied under gypsum soil c.onditic)n 1n a way that AIÂ Fateb varie.ty was superior on lpa 99 in feature Qf dty weight leave areas, absolute growth rate,. relative product anrelative efficiency of fertilizer The r sults also showed negative effect of high levels of pbosphqrus .-anzinc on the most of :patmears studied at the two varieties.